Design and Synthesis of Sulindac New Derivitives as Possible Mutual Prodrug with Potential to Maximized Therapeutic Area - Ahmed Kareem Hussein Mubarak; Ahmed Wheed Radhi Alhasnaway; Haider F.S. Al-zubaidy (Institute of Medico-legal Publications Pvt Ltd, 2021)
The urgent necessity today for development of anti cancer agent is crucial so highly dependent for searchingfor new anti neoplastic action ,the drug discovery process is costly and consume long time ,in my studyfocusing my efforts toward drug optimization process using sulindac (NSAID) which has a fantasticattractive area as anti cancer and anticancer in addition to it is anti inflammatory action .The study describes design and synthesis of mutual pro-drug of sulindac in combination with thenaturalanti oxidants (menthol ,thymol ,vanillin,guiacol) as a single integral pharmaceutical unit byan chloro acetylchlorideas spacer to form an ester mutual prodrug with expected to improve the anti inflammatory ,anticancer , antioxidant action of sulindac by the conjugation with natural anti oxidative integral moiety andminimized the ulcerogenic adverse effect of sulindacit is carboxylic acid functionality .The synthesis isconferred byH1NMR, FT-IR, CHN and physiochemical properties.